Unveiling the Dynamics of Malaysian Viewers’ Continuance Usage Intention of OTT Platforms: Insights from the Stimulus-Organism-Response (SOR) Paradigm - Lo, May Chiun; Abang Azlan, Mohamad; Wan Hashim, Wan Ibrahim; Thong, Jun Zhou (Emerald Publishing Limited, 2024)
This study aims to investigate how over-the-top (OTT) media services affect 10 consumers' demands for value, convenience, visual experience, and their ability to advance 11 media communications. This study also examines the constructs that impact viewers' 12 satisfaction and subsequently lead to continuance usage intention of OTT platforms. Using the 13 Stimulus-organism-response (SOR) model as the theoretical basis, the present study constructs 14 include content quality, accessibility, entertainment, hedonic value, attitude, satisfaction, and 15 continuance usage intention of OTT platforms.